The Influence of Origen to John Scottus Eriugena about ‘The Return of All Things to God’ - Artemi, Eirini (De Medio Aevo, 2014)
One of the most criticized doctrines held by Origen is his belief in a universal salvation. For Origen, to affirm a belief in an eternal hell over which the devil had dominion was to become dualistic by making the devil a god in his own right. Because Origen was very concerned with Gnostic beliefs and sought to counter them, when he speaks of salvation he explains that the satan is not equal to God, so the Satan will not be the winner in the end. For him, the focus is on God and the individual. Within Christian theology, especially of the medieval period, there has been a dialectic between those thinkers who attempt to follow Aristotle and those who see greater promise in neo-Platonism. The works of John Scottus Eriugena demonstrate that he was strongly influenced by Origen and his thoughts. To find the influence from Origen’s work on John Scottus Eriugena, we will expose the basic differences and similarities of the work of John Scottus Eriugena with the works of Origen. John was not only influenced by Gregorius of Nyssa but in fact by Origen. For this reason, both theologists refer to return of all things to God. Origen’s thought through the works of Augustine had influenced one more time John Scottus Eriugena.